Rural Tourism Development: Rumah Gadang As A Homestay In Traditional Village Of Nagari Sijunjung A Commodification - Ermayanti Ermayanti; Edi Indrizal; Ade Irwandi (Universitas Andalas, 2023)
The purpose of this paper is show that the commodification process that occurs in the Sijunjung Traditional Village to support the development of rural tourism. The process of commodification can be seen in the utilization of the Rumah Gadang as a place to stay (homestay) for visitors. Rumah Gadang for the Minangkabau people is not just a place to live but a cultural space and symbol. So that if it is made into a homestay it will create a dilemma, on the one hand, the Rumah Gadang needs to be maintained as a distinctive Minangkabau cultural monument and on the other hand, the tourism aspect can have an economic impact on the Sijunjung community. It is this dualism of Rumah Gadang as a cultural product and a tourism product that results in commodification to develop tourism in rural areas. The method used is a thorough observation of the Rumah Gadang and interviewing the residents and Ninik Mamak (traditional ruler) as members of the tribe that owns the Rumah gadang. A total of 15 Rumah Gadang have become homestays under the auspices of BCA bank CSR and are managed by the Nagari Sijunjung Traditional Village Management Agency (BP). Apart from that, Rumah Gadang still functions as a place and space for the social and cultural activities of the Sijunjung people. So that the values and norms that exist in the Rumah Gadang as a symbol of Minangkabau culture continue to run and through homestays, the Sijunjung community can get additional economic benefits from the tourism sector.